Manual of clinical paramedic procedures - Gregory, Peter; Mursell, Ian (Wiley-Blackwell, 2010)
Clinical procedures are a fundamental aspect of care for practitioners working in pre-hospital settings. This book helps paramedics to deliver effective, patient-focused care. It looks at topics including Aseptic Technique, Airway Management, Assisted Ventilation, Cardiopulmonary Resuscitation, Defibrillation and External Cardiac Pacing, and more.